A multicenter RCT of noninvasive ventilation in pneumonia-induced early mild acute respiratory distress syndrome - He, Hangyong; Sun, Bing; Liang, Lirong; Li, Yanming; Wang, He; Wei, Luqing; Li, Guofeng; Guo, Shuliang; Duan, Jun; Li, Yuping; Zhou, Ying; Chen, Yusheng; et al. (Critical care (London, England), 2019)
Rationale Our pilot study suggested that noninvasive ventilation (NIV) reduced the need for intubation compared with conventional administration of oxygen on patients with “early” stage of mild acute respiratory distress syndrome (ARDS, PaO 2 /FIO 2 between 200 and 300). Objectives To evaluate whether early NIV can reduce the need for invasive ventilation in patients with pneumonia-induced early mild ARDS. Methods Prospective, multicenter, randomized controlled trial (RCT) of NIV compared with conventional administration of oxygen through a Venturi mask. Primary outcome included the numbers of patients who met the intubation criteria. Results Two hundred subjects were randomized to NIV ( n = 102) or control ( n = 98) groups from 21 centers. Baseline characteristics were similar in the two groups. In the NIV group, PaO 2 /FIO 2 became significantly higher than in the control group at 2 h after randomization and remained stable for the first 72 h. NIV did not decrease the proportion of patients requiring intubation than in the control group (11/102 vs. 9/98, 10.8% vs. 9.2%, p = 0.706). The ICU mortality was similar in the two groups (7/102 vs. 7/98, 4.9% vs. 3.1%, p = 0.721). Multivariate analysis showed minute ventilation greater than 11 L/min at 48 h was the independent risk factor for NIV failure (OR, 1.176 [95% CI, 1.005–1.379], p = 0.043). Conclusions Treatment with NIV did not reduce the need for intubation among patients with pneumonia-induced early mild ARDS, despite the improved PaO 2 /FIO 2 observed with NIV compared with standard oxygen therapy. High minute ventilation may predict NIV failure. Trial registration NCT01581229 . Registered 19 April 2012